A Silica‐Aerogel‐Reinforced Composite Polymer Electrolyte with High Ionic Conductivity and High Modulus. Issue 32 (25th June 2018) - Lin, Dingchang; Yuen, Pak Yan; Liu, Yayuan; Liu, Wei; Liu, Nian; Dauskardt, Reinhold H.; Cui, Yi
Abstract: High‐energy all‐solid‐state lithium (Li) batteries have great potential as next‐generation energy‐storage devices. Among all choices of electrolytes, polymer‐based systems have attracted widespread attention due to their low density, low cost, and excellent processability. However, they are generally mechanically too weak to effectively suppress Li dendrites and have lower ionic conductivity for reasonable kinetics at ambient temperature. Herein, an ultrastrong reinforced composite polymer electrolyte (CPE) is successfully designed and fabricated by introducing a stiff mesoporous SiO2 aerogel as the backbone for a polymer‐based electrolyte. The interconnected SiO2 aerogel not only performs as a strong backbone strengthening the whole composite, but also offers large and continuous surfaces for strong anion adsorption, which produces a highly conductive pathway across the composite. As a consequence, a high modulus of ≈0.43 GPa and high ionic conductivity of ≈0.6 mS cm −1 at 30 °C are simultaneously achieved. Furthermore, LiFePO4 –Li full cells with good cyclability and rate capability at ambient temperature are obtained. Full cells with cathode capacity up to 2.1 mAh cm −2 are also demonstrated. The aerogel‐reinforced CPE represents a new design principle for solid‐state electrolytes and offers opportunities for future all‐solid‐state Li batteries. Abstract : High ionic conductivity and high modulus are simultaneously achieved in a polymer‐based lithium‐ion conductor by introducing a SiO2 aerogel network as a mechanical reinforcement. The large continuous surface, ultrahigh porosity, and the acidic surface chemistry of SiO2 uniquely bring about further enhanced room‐temperature ionic conductivity (≈0.6 mS cm −1 ), while its highly stiff nature promises over tenfold increase in elastic modulus (≈0.43 GPa).